"A country boy can survive:" Rural culture and male-targeted suicide prevention messaging. (November 2021) - Ewert, Rebecca
Abstract: The low rate of help-seeking and high rate of suicide completion among men has prompted public health officials to create suicide prevention campaigns that specifically target men. Drawing from data collected as part of a larger study of fire recovery in a rural county in Northern California, this paper utilizes 68 interviews with fire survivors (24 men and 44 women) and 40 interviews with mental health service providers to examine how rural residents interpret this type of campaign. To track patterns of help-seeking over time, I also draw upon 26 follow-up interviews – 20 with fire survivors (7 men and 13 women) and 6 with service providers – conducted one year after the first wave of interviews. In total, 134 in-depth interviews were conducted. This paper also draws on a secondary data source; I conducted content analysis of an internal Health and Human Services Agency focus group report used in the development of a local male-targeted suicide prevention campaign, Captain Awesome . As I show, male-targeted suicide prevention efforts have little salience in rural communities in which treatment resources are limited and stigma abounds. Perceptions about material conditions – i.e., treatment resources being few and far between – contribute to residents establishing a norm of not seeking help. Rural culture which emphasizes self-sufficiency and independence contributes to a pattern of both men and women repeating a narrative that frames men who seek help as weak. While research has identified women as key drivers for men's physical health maintenance, my research suggests that the same pattern might not hold around mental health maintenance in rural settings. In sum, I argue that male-targeted campaigns have limited resonance and efficacy in rural communities where material conditions and cultural narratives create physical and psychological barriers to accessing to treatment. Highlights: Male-targeted suicide prevention campaigns have little salience in rural areas. Perceptions of limited treatment resources contribute to low rates of help-seeking in rural places. A rural ethos emphasizing self-sufficiency contributes to low help-seeking. Both men and women residents of rural places reinforce stigma against help-seeking. Suicide prevention campaigns need to be developed with regional specificity.